Historiografi Islam Klasik Metode Riwayat dan Tematik dalam Historiografi Islam Klasik: Studi Komperatif atas Karya al-Thabari dan al-Mas’udi - Nafi, Moh. Iqbal; Badrun, Badrun; Amri, Nizar (Qurthuba: The Journal of History and Islamic Civilization, 2025)
This study explores the historiographic methods of two important figures in the tradition of writing classical Islamic history, namely al-Thabari and al-Mas'udi. This study aims to compare their methodological approaches in reconstructing history. Al-Thabari wrote Tarikh al-Umam wa al-Muluk using the method of history and chronological approach (hawliyat), paying great attention to the sanad and listing the narrators systematically. In contrast, al-Mas'udi in Muruj al-Dzahab wa Ma'adin al-Jauhar used the thematic method (al-tashnif al-maudhu'i) and geographical approach and emphasized narration and direct observation from the results of rihlah to various regions. Nevertheless, both of them made a major contribution to the development of Islamic historiography by presenting interpretations and historical narratives that were not only chronological but also reflective of the socio-cultural realities of their times. This study uses a qualitative and historical approach to explore primary and secondary sources related to their historiographical methods. The results show that the differences in their methods reflect the diversity of approaches in writing classical Islamic history.